BEBERAPA FAKTOR PENYEBAB KEJADIAN HIPERGLIKEMIA - Prasetyo, Agus; Abilowo, Ashar; Abidin, M Zainal; Astuti, Yuni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Hyperglycemia has become one of the major health problems that are increasingly encountered worldwide, especially since the incidence of this disease continues to show an increase from year to year. The general objective of this study were several factors that cause the incidence of hyperglycemia. The research design used in this study was Cross Sectional. The research was conducted in the Binangun Health Center working area. The research was conducted in December 2023. The population is all elderly people aged more than 60 years who live in the Binangun Health Center working area. The sample amounted to 55 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed a relationship between obesity (p value: 0.012) and diet (p value: 0.026) to hyperglycemia. It is recommended to the health center, to provide education or information about the importance of maintaining a good diet, as well as providing health counseling about diabetes mellitus.Keywords: Hyperglycemia, Obesity, Diet.